The Self-Control of Becky in the Movie The Wrath of Becky - Adella Adella; Zakridatul Agusmaniar Rane; Fina Amalia Masri; Arman (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2025)
The importance of self-control in society is to direct someone in a better direction, avoid committing crimes and can make someone get a new identity. This research used psychoanalysis theory of Sigmund Freud especially the id, ego and superego. The methodology of this research was qualitative descriptive, the data come from the movie entitle The Wrath of Becky. Data for this research was collected by watching, taking notes, identifying and then analyzing by presenting, describing and interpreting the data, as well as concluding the results of the analysis. From the results of the analysis, researcher found that the movie has a psychoanalytic aspect to the main character Becky, so that this movie has aspects of id, ego and superego. Becky's self-control was successful because the researcher found that Becky's personality was dominated by the role of the superego which can accommodate the desires of the id so that Becky did not take actions that were detrimental to herself and the people around her. Becky chose to obey the rules and the norms that exist in society. Of the three aspects of Sigmund Freud's psychoanalysis, it turned out that they are all covered in the movie The Wrath of Becky. Becky clearly reflects these aspects through her dialogue, facial expressions and her actions. Based on the above results, it can be concluded that Becky's self-control can make her not commit the crime and also that self-control makes Becky look like a teenager in general who does not have mental disorders.